Densitas dan Kandungan Total Lipid Mikroalga Spirulina platensis Yang Dikultur pada Tingkatan Perbedaan Fotoperiod - Manullang, Cristiana; Widianingsih, Widianingsih; Endrawati, Hadi (977-2407769)
Spirulina platensis is belong to divisi of Cyanophyta which has ability for good adaption in fluctuativ condition where environment factors can influent the composisition of nutrion (lipid, protein, carbohydrate). Lipid has function for fatty acid resources, vitamins and for bioenergy resources. This research aims to know influence of photoperiod with density and total lipid microalga Spirulina platensis which is has been cultured in different photoperiod as a purpose. This research uses complete random plan and treatment of photoperiod 4 hours light 20 hours dark, 8 hours ligth 16 hours dark, 12 hours light 12 hours dark, 24 hours light. The results shows that the highest density of S.platensis on experiment 24 hours light is 1591± 16 x 103 sinusoidal/mL and lowest density on photoperiod 4 hours light 20 hours dark 1087 ± 62 x 103 sinusoidal/mL while higest total lipid amount presentation of lipid on photoperiod 4 hours light 20 hours dark 46,08 ±27,93 %-dw and the total lipid 24 hours light treatment is 24,76 ±5,23 %-dw.